2021
DOI: 10.1038/s41556-021-00742-6
|View full text |Cite
|
Sign up to set email alerts
|

Release of Notch activity coordinated by IL-1β signalling confers differentiation plasticity of airway progenitors via Fosl2 during alveolar regeneration

Abstract: While the acquisition of cellular plasticity in adult stem cells is essential for rapid regeneration after tissue injury, little is known about the underlying mechanisms governing this process. Our data reveal the coordination of airway progenitor differentiation plasticity by inflammatory signals during alveolar regeneration. Upon damage, IL-1β signalling-dependent modulation of Jag1/2 expression in ciliated cells results in the inhibition of Notch signalling in secretory cells, which drives reprogramming and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 64 publications
3
60
0
Order By: Relevance
“…Therefore, we aimed to evaluate the functional role of EAAs in directing the fate conversion of secretory cells into DATP‐AT1 cells using an ex vivo three‐dimensional (3D) organoid culture system. We recently identified KDR/FLK1 as the surface marker of airway secretory cells (Choi et al , 2021 ; Jiang et al , 2021 ). Using this marker, we isolated secretory cells (KDR + EpCAM + ) from Lats1/2 dKO lungs, followed by organoid coculture with stromal cells (Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we aimed to evaluate the functional role of EAAs in directing the fate conversion of secretory cells into DATP‐AT1 cells using an ex vivo three‐dimensional (3D) organoid culture system. We recently identified KDR/FLK1 as the surface marker of airway secretory cells (Choi et al , 2021 ; Jiang et al , 2021 ). Using this marker, we isolated secretory cells (KDR + EpCAM + ) from Lats1/2 dKO lungs, followed by organoid coculture with stromal cells (Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Using a Sftpc + ATII depletion mouse model, it was concluded that there are more Sftpc + ATII cells derived from alveolar ATII cells than from BASCs [ 15 ]. However, a recent study found that mouse Scgb1a1 derived Sftpc + BASCs (also termed secretory ATII cells, sAT2 cells) are capable of long-term self-renewal, more so than residual AT2 cells in in vitro organoids [ 16 ]. It remains unknown in lung fibrosis if ATII cell depletion occurs within fibrotic area or if BASCs or the remaining ATII cells are the major source for regeneration of ATII cells in the alveoli.…”
Section: Introductionmentioning
confidence: 99%
“…Besides BASCs, studies have shown that club cells [ 3 ], BCs, integrin α6β4 positive cells, H2-K1 high, and Uroplakin3a ( Upk3a ) expressing airway epithelial progenitors can migrate to the alveoli and give rise to ATII cells under conditions of severe injury that involve broad epithelial denudation [ 17 21 ]. An abnormal cluster of Fstl1 + secretory cells were found during defective club cells (or secretory cells) transition to ATII cells [ 16 ]. These cells were marked by Id3, Porcn , and Cdkn1c and blocked the fate conversion from secretory to ATII cells when lacking sustained Notch activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations